Scanning Electron Microscopy and Geometric Contour Morphometry for Identifying Eggs of Three Amazonian Species of Mansonia (Diptera: Culicidae). Issue 3 (10th December 2019) - da Silva Ferreira, Francisco Augusto; Simões, Rejane de Castro; Ferreira-Keppler, Ruth Leila; Alencar, Jeronimo; Scarpassa, Vera Margarete; Tadei, Wanderli Pedro
Abstract: The eggs of three Amazonian species of the genus Mansonia (Diptera: Culicidae) were analyzed using morphological and morphometric characters. Eggs of Mansonia humeralis Dyar & Knab, 1916 were morphologically different from those of Mansonia titillans (Walker, 1848) and Mansonia amazonensis (Theobald, 1901), which were more similar to each other according to linear and geometric morphometry. A principal component analysis generated from elliptic Fourier contour data (PC1—92.6% and PC2—2.61%) indicated that Ma. amazonensis and Ma. titillans are more similar to each other than either is to Ma. humeralis . Discriminant multivariate analysis was highly accurate with only four classification errors and a 90% accuracy rate. The results indicate that the three Amazonian species can be precisely distinguished in the egg stage and that geometric morphometry based on elliptic Fourier contours is a promising method for distinguishing eggs of species of Mansonia . An identification key based on egg morphology is provided to distinguish the four Neotropical species.